BEYOND LECTURES - A QUALITATIVE INQUIRY INTO STUDENT EXPERIENCES AND VIEWS ON THE OPEN-DISCUSSION METHOD IN LEARNING ENVIRONMENTS - Teuku Azhari; Juwita Sahputri; Idaryani, Idaryani (Cirebon International Conference on Education and Economics Proceeding, 2024)
This study investigates the impact of open discussion methods on student learning in Indonesian language classes. Two research questions were explored: 1) how does open discussion influence student motivation? and 2) how does it affect active student participation? Quantitative data was collected from two classes of approximately 34 students each using a survey instrument containing 12 questions (6 for each research question). Statistical analysis revealed positive influences of open discussion methods on both student motivation (mean score = 4.26, SD = 0.92) and active participation (mean score = 4.26, SD = 1.13). The low standard deviations suggest relative consistency in students’ perceptions of these benefits. Overall, this study adds to the understanding of factors promoting positive student learning experiences and outcomes, specifically through the implementation of open discussion methods.